Aloe vera (Aloe barbadensis Miller) supplemented probiotic lassi prevents Shigella infiltration from epithelial barrier into systemic blood flow in mice model. (January 2017) - Hussain, Shaik Abdul; Patil, Girdhari Ramdas; Reddi, Srinu; Yadav, Vidhu; Pothuraju, Ramesh; Singh, Ram Ran Bijoy; Kapila, Suman
Abstract: The aim of present work was to investigate preventive role of orally administered Aloe vera supplemented probiotic lassi (APL) on Shigella dysenteriae infection in mice. At the end of experimental period (2, 5 and 7 days of challenging), different organs such as spleen, liver, small intestine, large intestine, and peritoneal fluid were collected and assessed for Shigella colonization. Secretary IgA was estimated in intestinal fluid. Blood was collected in heparinized tubes for various haematological studies. Oral administration of APL showed a significant ( p  < 0.05) reduction in the Shigella counts (log cfu/mL) in all organs as compared to other treatment groups at different intervals after post feeding. Similarly, secretary IgA antibody levels (μg/mL) in intestinal fluid were significantly ( p  < 0.05) increased in case of APL fed mice. Further, feeding of APL also demonstrated a positive effect on different haematological parameters viz. Hb (gm %), RBC and WBC count. The results indicated the immunoprotective effects of APL against Shigella dysenteriae induced infection in mice. Highlights: Aloe vera probiotic lassi (APL) was effective against Shigella infection in mice. Oral administration of APL reduced Shigella counts in different organs of mice. sIgA antibody levels significantly increased intestinal fluid of mice fed with APL. APL feeding increased haematological parameters Hb level, RBC and WBC count in mice.